A Pain in the Fetus: Toward Ending Confusion about Fetal Pain - Benatar, David (Bioethics, 2001)
Are fetuses, at any stage of their development, capable of feeling pain? In his paper, ‘Locating the Beginnings of Pain’, Stuart Derbyshire argues that they are not. We argue that he reaches this conclusion by way of conceptual confusion, a misreading of the available scientific data and the inclusion of irrelevant data. Despite his assertion to the contrary, the work of most scientists in the area supports the conclusion that fetuses can feel pain. At the outset we examine the concept of pain and distinguish it from the allied concept of nociception, with which it is sometimes confused. With the relevant conceptual framework in place, we elucidate the problem of determining when, in its development, a human becomes capable of feeling pain. We then examine the available data showing how, on balance, it tends more to support than undermine the claim that fetuses of around 28 to 30 weeks' gestation are capable of feeling pain.